Nutritional evaluation of different silages to feed rabbits - Villa R., Rigoberto; Hurtado V., Jaime (Revista de Ciencias Agrícolas, 2016)
On the Quindío’s University experimental farm “Bengala”, located in the municipality of Filandia, Quindío, was carried out an assessment regarding to the weight increase of rabbits for meat, fed on fodder, (imperial grass (Axonopus scoparius (Flüggé) Kuhlm) mixed with meadow buttercup (Ranunculus acris L.), ramie (Boehmeria nivea L.) and morus/mulberry (Morus alba L.). A completely randomized design with five probing groups of rabbits consisting of five rabbits each was used. The group fed on imperial grass and meadow buttercup ensilage, had the highest increase of weight (141g/weekly). Whereas the group fed on simply fresh fodder had the lower mean weight (109g/weekly). Thereafter, the nutritional food sources which better response for rabbits were silages based on meadow buttercup, morus/mulberry and ramie.